BRINGING HISTORY TO REAL LIFE: ALTERNATIVE HISTORY LEARNING BASED ON FACTUAL, INTERPRETATIONS, RECONSTRUCTION, ZEITGEIST FOR REAL LIFE ACTIONS (FIRZA) - Fadilla, Firza Azzam; Wijaya, Daya Negri; Widiadi, Aditya Nugroho (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
The FIRZA (Factual, Interpretations, Reconstruction, Zeitgeist for Real Life Actions) document-based history learning model was developed based on history learning problems; a). Lack of understanding of historical concepts in teachers and students, b). Problems in history textbooks that contain elements of subjectivity, c). Lack of use of primary sources of history. The research method used is research and development (R&D) with the design of Dick & Carey (2015) and using communicative action theory as a foundation for developing the FIRZA learning model. The purpose of this research is to develop a document-based history learning model, namely with historical methodology, and coverage of historical skills strands. The result of the research is that the FIRZA learning model has 5 syntaxes. This model aims to train students' thinking through learning strategies and methods with historiography exercises and evaluation through document-based questions to support understanding of historical concepts, facts, and narrative skills. FIRZA learning model was developed for interactive and progressive learning by encouraging students to be able to imagine, live the spirit of the times, and dialogue with the symptoms of past events to support historical awareness and implementation of historical thinking skills in real action. The results of this study are; 1). FIRZA learning model is effective for use in school education and higher education; 2). The results of this learning model can support the effectiveness of historical teaching materials for students with data ranging from 95% of students being able to understand and contextualize the material learned in real life.